The Effect of the Clustering Technique on Students’ Writing Ability in Descriptive Texts - Miranda Kristin Lumban Tungkup; Vercelly Hot Taruli Manik; Sarah Priscilla Silitonga; Esra Delima Hutabarat; Dumaris Silalahi (JURNAL PENDIDIKAN BAHASA, 2025)
One of the critical skills that one must have when learning English as a Foreign Language (EFL) at the junior high school level is writing descriptive texts. Nevertheless, it is still observed that a significant number of seventh-grade students have problems with the development and structuring of ideas in a coherent way when composing descriptive texts. The research was intended to examine how the clustering technique influences the writing skills of students in the descriptive texts. The study adopted a quantitative methodology, and it was designed as a quasi-experimental one. The sample was all the students of SMP Swasta Cinta Rakyat 3 Pematangsiantar in the seventh grade in the 2025/2026 academic year (two classes were used as a sample). The experimental group was given as Class VII-C (30 students) which was taught through clustering technique and Class VII-D(30 students) as the control group which was taught through a conventional teaching technique. The items were pre-tested and post-tested and a t-test was conducted to analyze the data. The findings indicated that the experimental group improved significantly, and the mean score rose to 80.10 compared to 63.73, whereas the mean score increased to 71.53 compared to 39.06 in the control group. The t-value (4.86) was above the t -table value (1.665) at the 0.05 level of significance, which meant that there was a statistically significant difference between the two groups. The results of these studies show that the clustering method is useful in increasing the success of junior high school students in writing descriptive texts in EFL classrooms.